Partial nephrectomy margin imaging using structured illumination microscopy. Issue 3 (5th October 2017) - Wang, Mei; Tulman, David B.; Sholl, Andrew B.; Mandava, Sree H.; Maddox, Michael M.; Lee, Benjamin R.; Quincy Brown, J.
Abstract : Partial nephrectomy (PN) is the recommended procedure over radical nephrectomy (RN) for patients with renal masses less than 4 cm in diameter (Stage T1a). Patients with less than 4 cm renal masses can also be treated with PN, but have a higher risk for positive surgical margins (PSM). PSM, when present, are indicative of poor clinical outcomes. The current gold‐standard histopathology method is not well‐suited for the identification of PSM intraoperatively due to processing time and destructive nature. Here, video‐rate structured illumination microscopy (VR‐SIM) was investigated as a potential tool for PSM detection during PN. A clinical image atlas assembled from ex vivo renal biopsies provided diagnostically useful images of benign and malignant kidney, similar to permanent histopathology. VR‐SIM was then used to image entire parenchymal margins of tumor resection covering up to >1800× more margin surface area than standard histology. Aided by the image atlas, the study pathologist correctly classified all parenchymal margins as negative for PSM with VR‐SIM, compared to standard postoperative pathology. The ability to evaluate large surgical margins in a short time frame with VR‐SIM may allow it to be used intraoperatively as a "safety net" for PSM detection, allowing more patients to undergo PN over RN. Abstract : Positive surgical margins (PSM) are rare in patients treated with partial nephrectomy (PN), but PSM potentially result in poor clinical outcomes. We demonstrate video‐rate structured illumination microscopy as a potential tool to detect PSM intraoperatively during robotic partial nephrectomy. We demonstrated the ability to capture the full parenchymal margin surface from fresh uncut PN specimens with microscopic resolution within a 15 to 30‐min time frame.